Conotoxins: Structure, Therapeutic Potential and Pharmacological Applications - Mir, Rafia; Karim, Sajjad; Amjad Kamal, Mohammad; M. Wilson, Cornelia; Mirza, Zeenat (Current Pharmaceutical Design, 2016)
Cone snails, also known as marine gastropods, from Conus genus produce in their venom a diverse range of small pharmacologically active structured peptides called conotoxins. The cone snail venoms are widely unexplored arsenal of toxins with therapeutic and pharmacological potential, making them a treasure trove of ligands and peptidic drug leads. Conotoxins are small disulfide bonded peptides, which act as remarkable selective inhibitors and modulators of ion channels (calcium, sodium, potassium), nicotinic acetylcholine receptors, noradrenaline transporters, N-methyl-D-aspartate receptors, and neurotensin receptors. They are highly potent and specific against several neuronal targets making them valuable as research tools, drug leads and even therapeutics. In this review, we discuss their gene superfamily classification, nomenclature, post-translational modification, structural framework, pharmacology and medical applications of the active conopeptides. We aim to give an overview of their structure and therapeutic potential. Understanding these aspects of conopeptides will help in designing more specific peptidic analogues.
Keywords: Conotoxins